2013
DOI: 10.1172/jci68189
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cell development is regulated by a STAT/IRF-8 axis

Abstract: Myeloid-derived suppressor cells (MDSCs IntroductionA major barrier to effective cancer immunotherapy is immune suppression, and the accumulation of myeloid-derived suppressor cells (MDSCs) has recently been recognized as a major mechanism to promote immune suppression (1, 2). MDSCs comprise a mixture of myeloid cells reflecting various stages of differentiation, and in mouse models, these cells are typically distinguished from other inhibitory myeloid populations based on their unique coexpression of macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
304
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(333 citation statements)
references
References 54 publications
25
304
1
Order By: Relevance
“…Interestingly, there appears to be a consensus regarding activation of Janus kinase protein and STAT 3 and 5 (47). Indeed, some reports argue that STAT 3 and 5 regulate MDSC function in both mice and humans (9,10,48 (20). Thus, these findings appear to be important in terms of MDSC induction by mTOR inhibitors or other immunosuppressive drugs in the context of clinical organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there appears to be a consensus regarding activation of Janus kinase protein and STAT 3 and 5 (47). Indeed, some reports argue that STAT 3 and 5 regulate MDSC function in both mice and humans (9,10,48 (20). Thus, these findings appear to be important in terms of MDSC induction by mTOR inhibitors or other immunosuppressive drugs in the context of clinical organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of CD45.2 ϩ cell, CD11b ϩ Gr1 ϩ cell, and BrdU ϩ cell were evaluated by flow cytometry. MDSC Depletion-G-MDSC depletion was performed as described previously (44). Briefly, anti-Ly6G antibody (1A8) or anti-IgG antibody (rat IgG2b) was injected (120 g per injection) through the tail vein on days 0 and 3 at post-Dex injection.…”
Section: Methodsmentioning
confidence: 99%
“…Transforming growth factor β (TGFβ), G-CSF and interferon β (IFNβ) are the most well-studied molecules in this process. TGFβ and G-CSF activate a tumor-and metastasispromoting program 25,27,65,[85][86][87][88] , by regulating the transcription factors inhibitor of DNA 1 (ID1), retinoblastoma 1 (RB1) and interferon regulatory factor 8 (IRF8) that control the immunosuppressive functions of neutrophils 25,87,89,90 . IFNβ acts as a negative regulator of the pro-tumorigenic phenotype of neutrophils 91,92 .…”
Section: Tumor-induced Neutrophil Polarization and Activationmentioning
confidence: 99%
“…Neutropenia predisposes patients to life-threatening infections, therefore recombinant G-CSF or GM-CSF is commonly prescribed to counteract reduced neutrophil numbers brought on by chemotherapy and to lessen therapy-induced mortality 190,191 . However, experimental studies indicate that G-CSF polarizes neutrophils towards a pro-tumorigenic phenotype and promotes metastasis formation [25][26][27][28]87 . Two experimental studies examining tumor growth after combining chemotherapy with G-CSF neutralization reported contradictory results 28,192 , leaving the debate open.…”
mentioning
confidence: 99%